AN ANALYSIS OF CODE SWITCHING USED BY EMILY COOPER IN THE SERIES EMILY IN PARIS SEASON 1 (2020) - Lamabelawa, Muharram Tuan Pati Naren; Nurhamidah, Idha (Jurnal Ilmiah Sultan Agung, 2024)
This research analyzes the code-switching behavior of the character Emily Cooper in the series